2007
DOI: 10.1097/bot.0b013e31814b822e
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Oriented Femoral Neck Fractures: Mechanical Analysis of Four Fixation Techniques

Abstract: The strongest construct for stabilizing a vertical shear femoral neck fracture is the proximal femoral locking plate, followed in descending order by the dynamic condylar screw, the dynamic hip screw, and the 3 cannulated screw configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
164
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(168 citation statements)
references
References 23 publications
3
164
0
1
Order By: Relevance
“…Aminian and colleagues compared fixation of vertically oriented femoral neck fractures in cadaver femurs with cannulated screws, a gliding hip screw, a condylar hip screw and a proximal femoral locking plate (n = 8 in all groups) (Aminian et al 2007). They found that all femurs operated with three cannulated screws failed during incremental loading to 1,400 N. These constructs were considered failures due to a lateral protrusion of the screws of 5 mm and varus displacement of the femoral head.…”
Section: Study Imentioning
confidence: 99%
See 2 more Smart Citations
“…Aminian and colleagues compared fixation of vertically oriented femoral neck fractures in cadaver femurs with cannulated screws, a gliding hip screw, a condylar hip screw and a proximal femoral locking plate (n = 8 in all groups) (Aminian et al 2007). They found that all femurs operated with three cannulated screws failed during incremental loading to 1,400 N. These constructs were considered failures due to a lateral protrusion of the screws of 5 mm and varus displacement of the femoral head.…”
Section: Study Imentioning
confidence: 99%
“…Over the last ten years, locking plates for use in femoral neck fractures have been introduced (Aminian et al 2007, Berkes et al 2012, Lin et al 2012, Nowotarski et al 2012. Locking plate technology was first introduced to bridge and stabilize long bone fractures as an alternative to compression plate fixation (Egol et al 2004).…”
Section: Locking Plate Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aminian et al [49] showed that the locking plate was the stronger and most stable construct when compared to three 7.3 mm cannulated screws, the sliding hip screw, and the dynamic condylar screw for fixation of Pauwels Type III fractures. The dynamic condylar screw was next in strength and stability, followed by the sliding hip screw and the cannulated screws.…”
Section: Implant Choicementioning
confidence: 99%
“…Sin embargo, algunos autores, basados en estudios biomecánicos, prefieren el tornillo deslizante de cadera en las fracturas con trazos inestables, debido a su mejor comportamiento respecto a los tornillos canulados de 6,5 mm. [22][23][24] en nuestra serie, se evaluaron solo los casos en los que se utilizaron tornillos canulados de 6,5 mm con rosca de 16 mm o 32 mm, y se excluyeron dos casos en los que se prefirió el tornillo deslizante de cadera, debido la verticalidad del trazo.…”
Section: 18-20unclassified